1945
DOI: 10.1021/ja01219a015
|View full text |Cite
|
Sign up to set email alerts
|

American Musk. III. The Scent of the Common Skunk

Abstract: The scent of the common skunk (Mephitis mephitis) is so extraordinarily powerful and persistent that from time to time it has attracted attention from chemists. That some sulfur compound was present was recognized early,1 but it remained for Aldrich2 to show that the principal odoriferous material is «-butyl mercaptan, accompanied by alkyl sulfides. Almost simultaneously Beckmann3 noted the occurrence of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1950
1950
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…However, carbonium ion reactions readily explain the formation of cycloparaffins in at least two ways: (1) when dienes are formed, as indicated by Thomas, cyclization can readily'• take place by addition of an olefin or another diene molecule, as in the now well-known Diels-Alder reactions, to form cyclohexenes and (2) many' instances of cyclization of dienes to cyclohexenes are known, these reactions taking place under mild polymerizing conditions or by the action of an acid catalyst. Stevens and Spalding (44,46) have suggested a carbonium ion mechanism for such cyclizations; moreover they have shown that in certain cases cyclopentane derivatives are formed, as in the conversion of 2,7-dimethyl-2,6-octadiene to a cyclopentane derivative, V As a rule, in such cyclizations, C6 rings are formed exclusively.…”
Section: Formation Of Cycloparaffinsmentioning
confidence: 99%
“…However, carbonium ion reactions readily explain the formation of cycloparaffins in at least two ways: (1) when dienes are formed, as indicated by Thomas, cyclization can readily'• take place by addition of an olefin or another diene molecule, as in the now well-known Diels-Alder reactions, to form cyclohexenes and (2) many' instances of cyclization of dienes to cyclohexenes are known, these reactions taking place under mild polymerizing conditions or by the action of an acid catalyst. Stevens and Spalding (44,46) have suggested a carbonium ion mechanism for such cyclizations; moreover they have shown that in certain cases cyclopentane derivatives are formed, as in the conversion of 2,7-dimethyl-2,6-octadiene to a cyclopentane derivative, V As a rule, in such cyclizations, C6 rings are formed exclusively.…”
Section: Formation Of Cycloparaffinsmentioning
confidence: 99%
“…The compounds containing the group RSCHC=C show ready cleavage of I I the carbon-sulfur bond under conditions which do not affect the analogous saturated sulfides. One example of this difference is the action of methyl iodide on allylic sulfides, which under mild conditions yield trimethylsulfonium iodide (140,269,374,395).…”
Section: C1ch2ch2ch2sr -Ch2-ch2mentioning
confidence: 99%
“…A Preliminary Note on the Scent Glands of the Beaver and feared losing credit for his own earlier work on beaver secretions 7 . I had in fact read Stevens' third instalment 8 in that series, The Scent of the Common Skunk, while engaging in what might have been my peak moment of domestic organic chemistry. In case you are wondering, instalments I and IV take up the scent of the muskrat.…”
Section: Molecular Backstoriesmentioning
confidence: 99%